TEKNOLOGI KEUANGAN DALAM INVESTASI PASAR MODAL - Ely Suhayati; Lisna Hikmahdiani (LP2M Universitas Bina Bangsa, 2022)
The purpose of this research is to find out capital market investment opportunities in the era of financial technology in Indonesia. This research uses quantitative methods and literature review where this research is a collection of data and previous research on global financial technology. The data collection techniques and instruments in the study used surveys and questionnaires by 40 respondents. The results of the study revealed that investment opportunities in the era of financial technology in Indonesia are quite large. In the era of financial technology and with a large number of internet users in Indonesia, it opens up a huge opportunity for people, especially the younger generation to invest and benefit for a brighter future. Therefore, with the investment, the interest of the younger generation who are technologically literate can make the business invest in advanced and developing capital markets